BL_GERICHTE 745 22 246 / 81 vom 15. März 2022 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 30. März 2023 (745 22 246 / 81) - BL Gerichte (2022)
Ergänzungsleistungen